Return to Play Following Isolated and Combined Anterior Cruciate Ligament Reconstruction: 25+ Years of Experience Treating National Football League Athletes. Issue 10 (22nd October 2020) - Khair, Michael; Riboh, Jonathan; Solis, Jaicus; Maurer, Jim; Brown, J. Britt; Vandermeer, Robert D.; Cooper, Daniel E.
Background: The first case series to report on return to play (RTP) in National Football League (NFL) players after primary anterior cruciate ligament (ACL) reconstruction (ACLR) published an RTP rate of 63%. Other studies that have attempted to estimate RTP after ACLR in these elite athletes have been largely based on secondary sources. This study is the second to report the authors' own results in treating ACL injuries in NFL players spanning a study period of 25+ years. Purpose: To report the senior authors' experience treating ACL injuries in NFL players as well as revisit the concept of RTP as it is currently used to measure successful surgical outcomes in professional athletes. Study Design: Case series; Level of evidence, 4. Methods: A total of 47 NFL players were treated at our institution for knee injuries that included a complete tear of the ACL; of these, 41 were primary ACLR and 6 were revision ACLR. Of the primary ACLRs, 6 were classified as ACL plus additional ligament and 3 were classified as multiligament. Return to game play (RTGP) was defined as returning to play in a regular-season game. Successful return to previous participation (RTPP) was defined as return to a level of participation equal to the level the player had reached before injury. Multivariate analysis was used to assess predictors of successful RTPP. Results: Using the RTGP criteria proposed by prior authors, the RTGP after primary ACLR was 73%. Using our proposed RTPP criteria, 87.8% of players successfully returned to the same level of participation after primary ACLR. RTGP percentage for all NFL players after ACLR (including multiligament injuries) was 67.6%, and the overall RTPP for those patients was 87.8%. In multivariate analysis, age ≤25 years was predictive of successful RTPP. High draft picks and offensive players played more seasons after primary ACLR. ACL graft rupture occurred in 4.3% of this cohort. Contralateral ACL tear occurred in 8.5%. Conclusion: Regardless of which definition is used to measure a successful outcome after ACLR surgery, the findings of this study suggest that successful return after primary ACLR in NFL athletes is higher than previously reported. While concomitant reconstruction of a single collateral ligament did not affect RTPP, revision ACLR or bicruciate plus collateral ligament reconstruction was associated with a lower RTPP rate. Age ≤25 years predicted successful RTPP. The risk of a future ACL tear of either knee after index reconstruction was approximately 13%.